دور التمويل المصرفي الإسلامي في تحقيق النمو الاقتصادي دراسة تحليلية قياسية- حالة السعودية (2014-2021) - شبرو السعيد; مهاوات محمد الطيب (University of Eloued جامعة الوادي, 2024)
"الملخص: حاولت هذه الدراسة قياس أثر التمويل المصرفي الإسلامي على التغير في النمو الاقتصادي في المملكة العربية السعودية للفترة 2014 Q1 -Q42021 ثم تقدير هذه العلاقة بين الناتج المحلي الاجمالي الحقيقي كمؤثر يعبر عن النمو الاقتصادي كمتغير تابع من جهة ومتغيرين تفسيريين واجمالي التمويل المصرفي الإسلامي المقدم من المصارف في المملكة العربية السعودية، ومتغير ضابط تمثل في مؤشر أسعار الاستهلاك من جهة أخرى ولتحقيق الأهداف الخاصة بالدراسة تم استخدام مجموعة من المقاربات وطرق واختبارات وأدوات القياس الاقتصادي من ذلك اختبار جذر الوحدة للسلاسل الزمنية واختبار التكامل المشرك بالاعتماد على منهج المحدود ولقد اعتمدنا على بناء نموذج قياسي تم تقديره وفق منهجية الانحدار الذاتي للفجوة الزمنية الموزعة ARDL لتقدير العلاقة في الامدين البعيد والقريب . ثم التوصل الى أن اجمالي التمويل المصرفي يرتبط بعلاقة توازنيه طويلة الأجل مع النمو الاقتصادي ,حيث تم التوصل الى أن حدوث زيادة في التمويل المصرفي الإسلامي نسبة 1 %سوف يؤدي الى زيادة الناتج المحلي الاجمالي المعبر على النمو الاقتصادي ب: 0.13% في الامد البعيد كما تم الوصول الى أن التمويل المصرفي الإسلامي ليس له تأثير على النمو الاقتصادي في المملكة العربية السعودية خلال فترة الدراسة . "This study aimed to measure the impact of Islamic banking financing on changes in economic growth in the Kingdom of Saudi Arabia for the period 2014-2021, and then estimate this relationship between real GDP as a proxy for economic growth as a dependent variable, on the one hand, and two explanatory variables: total Islamic banking financing provided by banks in the Kingdom of Saudi Arabia and a control variable represented by the consumer price index, on the other hand. To achieve the study's objectives, a variety of approaches, methods, tests, and economic measurement tools were used, including unit root tests, cointegration tests based on the bounds approach. A standard measurement model was constructed and estimated using the Autoregressive Distributed Lag (ARDL) methodology to estimate the relationship in the long and short run. The study concluded that total Islamic banking financing is associated with a long-run equilibrium relationship with economic growth. An increase of 1% in Islamic banking financing would lead to a 0.13% increase in real GDP representing economic growth in the long run. Additionally, it was found that Islamic banking financing does not have a significant impact on economic growth in the Kingdom of Saudi Arabia during the study period."
ماستر
Keywords: "التمويل المصرفي الإسلامي; النمو الاقتصادي; منهجية ARDL، تصنيف JEL: E52; E62; G32 "; Islamic banking financing; economic growth; ARDL methodology; JEL Classification: E52; E62; G32